Rehabilitation Surgery for Peripheral Facial Nerve Injury after Facial Trauma - An Quang Lam; Thuy Phan Chung Tran; Duong Van Tran; Hiep Xuan Tran; Albert J. Fox; Luan Viet Tran (International Archives of Otorhinolaryngology, 2024)
Introduction Facial trauma can cause damage to the facial nerve, which can have negative effects on function, aesthetics, and quality of life if left untreated.